MATERIALS AND TECHNOLOGIES FOR SURGICAL GUIDES - Cristian-Constantin Budacu; Norina Consuela Forna; Doriana Agop Forna; Razvan Leata; Antoanela Magdalena Covaci; Iulian Constantin (Romanian Journal of Oral Rehabilitation)
This review looks at the role of surgical guides in dental and maxillofacial surgery, highlighting the benefits and challenges associated with their use. Surgical guides are essential tools that allow surgeons to perform interventions with increased precision, thereby reducing risks and improving long-term outcomes. Made from biocompatible materials such as medical resins, polymers, and metal alloys, these guides are created using advanced technologies, including 3D printing and CAD software. In this context, the review examines the advantages of the guides, such as reducing operative time and minimizing trauma to tissues, as well as disadvantages, such as high costs and rigidity that limit intraoperative adaptability. Future research goals are also addressed, with a focus on biomaterials that can reduce inflammation and accelerate healing, as well as reducing production costs to increase accessibility. The findings suggest that surgical guides represent a major innovation, with the potential to become a standard in surgical practice due to their benefits in terms of safety, efficiency and adaptability. Continuous development in biomaterials and manufacturing technologies will significantly contribute to improving patient experience and surgical outcomes